Analisis Pengaruh Jumlah Penduduk, IPM dan Tingkat Pengangguran Terbuka Terhadap Tingkat Kemiskinan di Provinsi Jawa Timur - Ardina, Tiffany (Faculty of Economic an Business Wijaya Kusuma Surabaya University, 2024)
Poverty is a complex economic problem and is often faced by countries in the world. There are various factors that cause poverty, especially in Indonesia. This research aims to determine the influence of Population, Human Development Index, and Open Unemployment Rate on poverty levels in East Java Province. This research uses quantitative research and secondary data for the 2017 – 2022 time period obtained from the official portal of the East Java Province Central Statistics Agency. The analytical tool used is panel data regression using the selected Fixed Effect model. The results of this research show that the population variable does not have a significant effect on the poverty level in East Java Province, the human development index variable and the open unemployment rate variable have a significant effect on the poverty level in East Java Province. Meanwhile, simultaneously the variables of population, human development index, and open unemployment rate have a significant effect on the poverty level in East Java Province